(untitled) - Schaie, K. Warner; Willis, Sherry L (Upper Saddle River, NJ, 2002)
Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Adulthood; Life cycle, Human; Adulthood -- Psychological aspects; Aging -- Psychological aspects; Tuổi trưởng thành -- Tâm lý học ; Vòng đời con người